2017
DOI: 10.1007/s10995-017-2261-8
|View full text |Cite
|
Sign up to set email alerts
|

“It’s a Very Big Burden on Me”: Women’s Experiences Using Insulin for Gestational Diabetes

Abstract: Objectives Gestational Diabetes Mellitus (GDM) affects hundreds of thousands of women each year. Many require medications to manage their blood glucose levels. Only insulin is approved by the U.S. Food and Drug Administration for use in pregnancy. While other medications can be used, their safety remains controversial. Few studies have examined women's lived experience of using insulin for GDM. Our objective in this study was to foreground the voices of women speaking about their treatment experience. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
2
27
0
3
Order By: Relevance
“…According to the literature, concern for the baby is the strongest motivating factor for behaviour change during pregnancy [18, 40] and in our study provided motivation to make major lifestyle adjustments at any cost, including resisting cravings for unhealthy food and enduring the side effects of medication. Some respondents described negative experiences with antidiabetic therapy in keeping with previous reports that women with GDM find insulin use overwhelming and burdensome [16, 41, 51]. Yet in comparison to dietary modification, others prefer insulin use to manage GDM [40].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…According to the literature, concern for the baby is the strongest motivating factor for behaviour change during pregnancy [18, 40] and in our study provided motivation to make major lifestyle adjustments at any cost, including resisting cravings for unhealthy food and enduring the side effects of medication. Some respondents described negative experiences with antidiabetic therapy in keeping with previous reports that women with GDM find insulin use overwhelming and burdensome [16, 41, 51]. Yet in comparison to dietary modification, others prefer insulin use to manage GDM [40].…”
Section: Discussionmentioning
confidence: 59%
“…Several qualitative studies have explored women’s perspectives on GDM and lifestyle related behaviour change in North America and Europe [1621]. However, studies on women’s lived experiences of GDM in LMICs are still lacking [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from this study support and expand upon previous literature. Previous research exploring patient–provider communication about medication safety during pregnancy elucidated barriers facing patients, physicians, and pharmacists (Eisenberg et al, 2010; Figueroa Gray et al, 2017; Hammer & Burton-Jeangros, 2013; M. A. Morgan et al, 2010; Obican & Scialli, 2011; Santucci et al, 2010; Schwarz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These cultural trends have shifted the emphasis from the pregnant woman as the primary patient to the health of the fetus, above all. For example, in one study about insulin use to treat gestational diabetes, women reported feeling a “loss of control” over decisions in their care, and perceived the use of “scare tactics” in interactions with providers (Figueroa Gray, Hsu, Kiel, & Dublin, 2017). …”
mentioning
confidence: 99%
“…Furthermore, the medication experience involves the patient's reliance on and trust in the healthcare system and its providers. Not only do providers allow access to medications, but patients also need more information to feel comfortable about medication use [12,15,26,30,31,42,67]. Patients need a trusting relationship [27,36,39,40,66] with providers to engender a sense of security about their medications [11,44,52,72].…”
Section: Attributesmentioning
confidence: 99%